JUMLAH ANTI IDEAL FUZZY DARI NEAR-RING - Saman Abdurrahman (EPSILON: JURNAL MATEMATIKA MURNI DAN TERAPAN, 2014)
In this paper, the concept of addition of fuzzy anti ideal from the near-ring and prove the properties of the sum. The result of this study is the ideal anti-fuzzy addition of the near-ring, is the ideal anti-fuzzy of the near-ring.